(untitled) (Politeja, 2022)
Polish public diplomacy is a multilateral instrument of foreign policy, which represents Poland’s soft power. Numerous and developed Poland’s public diplomacy activities are in post-Soviet states, especially in Ukraine. This country plays a specific and important role in Poland’s foreign policy. The main fields of Poland’s public diplomacy in Ukraine are those connected with cultural, scientific and educational, as well as development aid issues. Apart from them, there is another field that is less addressed and studied by scholars – cooperation between partner cities. Such a field could be presented and examined separately in the frameworks of ‘city diplomacy’ and as a part of public diplomacy as well. This article presents an analysis of Polish-Ukrainian partner cities cooperation, using public diplomacy as a tool for establishing mutual understanding between people.